ANALISIS PENGARUH KEPERCAYAAN, JAMINAN RASA AMAN DAN AKSESIBILITAS TERHADAP MINAT MENABUNG NASABAH DI BANK BRI CABANG TENGGARONG - MELKY EKY CHRISTIAN (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2016)
The tight competition with private banking, limited human resources professionals, the lack of a sense of security customers, information technology and telecommunications continues to grow, the location is strategic, customers' needs for ease of service, as well as an increase in food prices is a major obstacle to the government bank in accommodating public funds. This prompted the Bank Rakyat Indonesia (BRI) seeks to develop strategies to attract and retain customers through increased interest in saving the customer. This study aimed to analyze the Influence of Faith, guarantee security, and Accessibility to customers Interest Savings Bank BRI branch in Tenggarong. The population in this study is the consumer of Bank BRI branch in Tenggarong. The sample size of 40 respondents using purposive sampling.The collection of data through questionnaires. Data analysis technique used is multiple linear regression. The hypothesis of this study showed that variables that trust, a sense of security to have a positive effect but not significant customer interest in bank savings BRI branch Tenggarong. While accessibility has positive and significant impact on the interest savings bank customer BRI branch Tenggarong.Keywords: Trust, Assurance Security, Accessibility and Interest Savings